Vizualne prezentacije pri pouku matematike - Tomšič Mavrič, Suzana (Matematika v šoli, 2012)
In the article we present eight worksheets designed for introducing certain mathematical concepts with the help of visual representations, which are carried out primarily with images or sequences of images. The possible positive effects of such an approach are commented with the help of three relevant articles presented in the introduction.
Keywords: delovni listi; mathematics instruction; pouk matematike; visual representations; vizualne prezentacije; worksheets